Variasi Ragam Hias Tumpal pada Nisan-Nisan Kuno di Kabupaten Lombok Tengah - Galih Pitaloka Sari; Ni Ketut Puji Astiti Laksmi; Zuraidah; Baiq Ellyse Iswandari Mustarita; Cornelia Ayu Caesaryanti Fajarria (Humanis, 2026)
This study explores the function and meaning of triangular decorative patterns (tumpal) on ancient tombstones in Central Lombok as a form of cultural heritage imbued with spiritual, aesthetic, social, and historical values. Using a descriptive qualitative approach and symbolic analysis, the research documents various motifs such as patra styled in jvala, winged sankha, padma, vegetal scrolls, and bamboo shoots, applied as both explicit and implicit tumpal forms. The findings reveal that these decorations serve magical, symbolic, aesthetic, and historical functions, as well as indicators of social stratification. Additionally, the motifs convey spiritual, cosmological, and life-death philosophy meanings deeply rooted in Lombok's local beliefs. The presence of Balinese and Hindu-Buddhist motifs on Islamic tombs indicates a strong cultural acculturation process. This study shows that decorative elements are not merely ornamental, but are visual representations of belief systems and cultural values passed down through generations.